2021
DOI: 10.1155/2021/3818652
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fracture Resistance of Endodontically Treated Teeth Restored with FiberSite Postsystem and Glass Fiber, Combined with Different Root Canal Sealers

Abstract: This study is aimed at evaluating the effects of FiberSite and glass fiber postsystems on the fracture resistance of endodontically restored teeth, when combined with various root canal sealers. Forty human mandibular premolar teeth, each having a single root with anatomically comparable dimension and length, were selected. The teeth in each experimental group ( n = 10 ) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…10 Laboratory and finite element analysis (FEA) studies also revealed that FP can protect remaining tooth structures against extensive fracture loads that can cause catastrophic (nonrestorable) failures. [11][12][13] They facilitate creating a monoblock restoration that acts as a single unit against masticatory forces. 14 It is of great importance to improve the prognosis of ETT with weakened roots facing higher fracture risk by obtaining a better monoblock structure.…”
Section: Introductionmentioning
confidence: 99%
“…10 Laboratory and finite element analysis (FEA) studies also revealed that FP can protect remaining tooth structures against extensive fracture loads that can cause catastrophic (nonrestorable) failures. [11][12][13] They facilitate creating a monoblock restoration that acts as a single unit against masticatory forces. 14 It is of great importance to improve the prognosis of ETT with weakened roots facing higher fracture risk by obtaining a better monoblock structure.…”
Section: Introductionmentioning
confidence: 99%